2008
DOI: 10.3402/ljm.v3i2.4763
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sympathetic Antagonists on the Antidepressant Action of Alprazolam

Abstract: Alprazolam is an anti-anxiety drug shown to be effective in the treatment of depression. In this study, the effect of sympathetic receptor antagonists on alprazolam–induced antidepressant action was studied using a mouse model of forced swimming behavioral despair. The interaction of three sympathetic receptor antagonists with benzodiazepines, which may impact the clinical use of alprazolam, was also studied. Behavioral despair was examined in six groups of albino mice. Drugs were administered intraperitoneall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…A plausible explanation for why non-cannabinoid drugs (i.e., mifepristone and propranolol) were ineffective is that the doses tested were simply insufficient to significantly affect withdrawal-induced behavior. However, dosing was based on published studies that demonstrated that these doses are sufficient to block the neuroendocrine stress response in mice (Al-tubuly et al, 2008; Chester et al, 2014; Kinsey et al, 2011; Lichtman et al, 2001). Thus, we speculate that THC withdrawal is a stressor that modulates the THC withdrawal-induced behaviors reported here, albeit not via catecholamine nor glucocorticoid receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A plausible explanation for why non-cannabinoid drugs (i.e., mifepristone and propranolol) were ineffective is that the doses tested were simply insufficient to significantly affect withdrawal-induced behavior. However, dosing was based on published studies that demonstrated that these doses are sufficient to block the neuroendocrine stress response in mice (Al-tubuly et al, 2008; Chester et al, 2014; Kinsey et al, 2011; Lichtman et al, 2001). Thus, we speculate that THC withdrawal is a stressor that modulates the THC withdrawal-induced behaviors reported here, albeit not via catecholamine nor glucocorticoid receptors.…”
Section: Discussionmentioning
confidence: 99%
“…All drugs were dissolved in a vehicle composed of 5% ethanol, 5% Kolliphor EL (Sigma-Aldrich, St. Louis, MO), and 90% saline (Kinsey and Cole, 2013), with the exception of mifepristone, which was dissolved in a vehicle of 10% DMSO (Sigma-Aldrich), 10% TWEEN 80, and 80% saline. Doses and pretreatment times were chosen based on previous experience and literature (Al-tubuly et al, 2008; Chester et al, 2014; Kinsey et al, 2011; Lichtman et al, 2001). JZL184 (8 mg/kg, i.p.…”
Section: Methodsmentioning
confidence: 99%
“…The observed decrease in defecation and urination in Old-AT mice compared to Old controls indicates a lower anxiety status in these animals. These results agree with the decreases in anxiety (Deary et al ., 1991 ) and depression (Al-Tubuly et al ., 2008 ) reported after treatment with atenolol in human patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is generally thought that immune cells have almost exclusively β-2 adrenergic receptors, there are results involving β-1 adrenergic receptor signaling in the modulation of immune responses (Emeny et al ., 2007 ), but their immunological relevance has been largely unexplored and the effect of atenolol on the immune cell functions has been scarcely studied. Concerning behavior, a few reports showed decreased anxiety (Deary et al ., 1991 ) and antidepressant effects (Al-Tubuly et al ., 2008 ) after atenolol treatment, but the impact of atenolol on behavioral parameters has not been investigated. In the case of the cardiovascular parameters, as an increase in mortality was detected only in very old individuals, the measurements were repeated at 35 months of age.…”
Section: Introductionmentioning
confidence: 99%
“…Monoaminergic, serotoninergic, and noradrenergic systems are known to play major roles in major depression (Perona et al, 2008). However, the GABA system also participates in the antidepressant actions of thiazole-BDZ such as ALP that, in addition to enhancing the release of serotonin (5-HT) in the hippocampus to produce antidepressant actions, may act by means of a GABAergic mechanism that is independent of the BDZ-site receptor (Jonas and Cohon, 1993;Kalueff and Nutt, 2007;Al-Tubuly et al, 2008). Thus, as may be observed in Fig.…”
Section: Tablementioning
confidence: 99%